The Measurement of the Total Excess Lifetime Cancer Risk in Soil Samples from Tar Al-Najaf in Al-Najaf Al-Ashraf-Iraq - Heiyam Najy Hady, Zahraa Mohammed Mashkor, (Pakistan Journal of Medical & Health Sciences, 2023)
ABSTRACT The radioactivity of the dissected earth formations of Tar Al-Najaf in Al-Najaf Al-Ashraf Governorate has been studied, which is considered one of the most important archaeological areas in the province, as Tar Al-Najaf is one of the natural phenomena prominently present in the governorate; it cuts sharply to form a rocky cliff, as well as overlooks from the southern end of a plateau Al-Najaf and on the sea of Al-Najaf, in a clear and surprising way, Al-Najaf flew, by selecting 50 sites to take samples from the region. Spectral measurements were made using a thallium-activated sodium iodide detector ( ). It was found that the specific activity of , and in the studied ranged between to with average , Bq.kg-1 to (8.356±1.013) with average (21.728) and (475.391 ± 7.870) to (95.173 ± 1.994) with average (281.197) respectively. The value of Absorbed Dose Rate in Air was also calculated, it was between (47.389) (nGy/h) to (16.366) (nGy/h) with average (34.950), the Annual Effective Dose between (0.234) (mSv/y) to (0.080) (mSv/y) with average (0.171), the Annual Effective Dose between (0.058) (mSv/y to (0.020) with average (0.0423),the excess lifetime cancer risk (in) between (0.0423) to (0.280) , with average ( 0.599), and the Excess lifetime cancer risk (out) between (0.205) to ( 0.070), with average (0.149). Comparing the present results with the globally considered values, it was found that the radiation levels of the studied samples are within the permissible limits. Keywards: Natural radioactivity, gamma spectrum, Nal(TI) detector , Tar Al-Najaf area .